Utilization of m-Phenylenediamine-Furfural Resin for Removal of Cu(II) from Aqueous Solution-A Thermodynamic Study - Tariq S. Najim; Israa G. Zainal; Dina A. Ali (E-Journal of Chemistry)
m-Phenylenediamine was condensed with furfural in absence of catalyst at room temperature. The produced m-phenylenediamine-furfural resin was used for the removal of Cu(II) from aqueous solution. The pH for the optimum removal of Cu(II) was 6. The negative values of Gibbs free energy at low concentration of Cu(II) (20, 30 ppm) indicative of the spontaneous adsorption process, while, at higher Cu(II) concentration (40,50 ppm) the positive and weak values of ∆G° indicate that the process is feasible but non spontaneous. The values of ∆H° were positive indicating that the sorption process is endothermic. On the other hand, the values of activation energy (Ea) were inconsistent with the values of ∆H° both are positive and lie in the range of physisorption. The entropy ∆S° of the process was positive indicative of the randomness of the Cu(II) ions at the solid / liquid interface. The values of sticking probability S* were less than one which indicate a preferable adsorption process and the mechanism is physisorption.